The Soil-Ecologic and Infrastructure Aspects of Agroproduction Development Strategy realization in Russia - A. L. Ivanov; S. N. Volkov; I. Yu. Savin (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The issues of improving land relations, rational land use and adaptation to climate are considered as the basic directions of the development strategy of the agro-industrial complex, discussed and supported by the Presidium of the RAS (18.04.2017). It is emphasized that the main determinant of a successful solution of all problems in modern land use management in Russia are measures to protect the soil cover, an adequate assessment of its condition and a fundamental change in land relations that the Federal Land Service should resolve. The consequences of the inconsistent implementation of land reform in the post-Soviet period, the main negative outcome of which are the latifundism of large agroholdings and companies, are shown. The resource potential of the modern land fund of the country is estimated to be one third less than the pre-perestroika one. The main direction in the development of agroproduction is modernization, intensification, development of land reclamation and chemicalization, which will allow us to reach, at a minimum, the average world yield level (3.5 tons / ha). The risks associated with the proposed land expansion (plowing) of land withdrawn from circulation, including marginal and badlands, are discussed. Examples of micromorphological indication of soil degradation and uncertainty associated with the detection of the results of modern space images analysis are shown. The necessity of actualization of information on soil degradation and assessment of suitability (favorability) for active agricultural production is substantiated.